2014
DOI: 10.1016/b978-0-12-800223-0.00004-9
|View full text |Cite
|
Sign up to set email alerts
|

Biology of the Major Facilitative Folate Transporters SLC19A1 and SLC46A1

Abstract: This chapter focuses on the biology of the major facilitative membrane folate transporters, the reduced folate carrier (RFC), and the proton-coupled folate transporter (PCFT). Folates are essential vitamins, and folate deficiency contributes to a variety of heath disorders. RFC is ubiquitously expressed and is the major folate transporter in mammalian cells and tissues. PCFT mediates intestinal absorption of dietary folates. Clinically relevant antifolates such as methotrexate (MTX) are transported by RFC, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 126 publications
(245 reference statements)
0
92
0
Order By: Relevance
“…The results of the present study showed that high expression of the two folate transport genes SLC19A1/RFC-1 and SLC46A1/PCFT in tumor tissue correlated with decreased risk of recurrent disease, measured as DFS. Both SLC19A1/RFC-1 and SLC46A1/PCFT belong to the superfamily of solute carriers, but are functionally distinct (26). The SLC19A1/RFC-1 gene encodes the reduced folate carrier which functions optimally at physiological pH, transferring reduced folates, including The expression levels for the two curves have been set one standard deviation above and one standard deviation below the mean, where one standard deviation corresponds to a fold change in log expression levels of 1.57.…”
Section: Ggh) and Folate Metabolism (Aldh1l1 Aldh1l2 Amt Atic Ftcmentioning
confidence: 99%
“…The results of the present study showed that high expression of the two folate transport genes SLC19A1/RFC-1 and SLC46A1/PCFT in tumor tissue correlated with decreased risk of recurrent disease, measured as DFS. Both SLC19A1/RFC-1 and SLC46A1/PCFT belong to the superfamily of solute carriers, but are functionally distinct (26). The SLC19A1/RFC-1 gene encodes the reduced folate carrier which functions optimally at physiological pH, transferring reduced folates, including The expression levels for the two curves have been set one standard deviation above and one standard deviation below the mean, where one standard deviation corresponds to a fold change in log expression levels of 1.57.…”
Section: Ggh) and Folate Metabolism (Aldh1l1 Aldh1l2 Amt Atic Ftcmentioning
confidence: 99%
“…Unlike RFC, PCFT operates optimally in acidic microclimates (pH 5-5.5) as those in the upper small intestine and tumor tissues [30,31]. RFC and PCFT are 400-600 amino acid transmembrane proteins consisting of 12 transmembrane domains [30,31]. The weak substrate affinity (μM Kd values) and high transport capacity of Note that equivalent sequence numbering for FRβ is incremented +16 relative to FRα.…”
Section: Interaction Between Frs and Antifolatesmentioning
confidence: 98%
“…b) The proton-coupled folate transporter (PCFT) mediates intestinal absorption of dietary folates and has equal affinities for reduced and oxidized folates [30,31]. Unlike RFC, PCFT operates optimally in acidic microclimates (pH 5-5.5) as those in the upper small intestine and tumor tissues [30,31].…”
Section: Interaction Between Frs and Antifolatesmentioning
confidence: 99%
See 2 more Smart Citations